Improving the Reading Literacy Culture of Islamic Elementary School Students in Pemalang, Indonesia - Khasanah, Riana Khomisatun; Ariyani, Dewi (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2023)
Reading literacy is a fundamental skill for everyone. This can be instilled from a young age. The Government of the Republic of Indonesia, through the Ministry of Education and Culture, issued Regulation Number 23 of 2015 on the Development of Student Characteristics. This policy forms the foundation for the School Literacy Movement program, which is intended to increase students' interest in reading and cultivate literacy. The purpose of this study is to analyze efforts to improve students' reading literacy culture at Madrasah Ibtidaiyah Dewi Masyithoh 02 Banyumudal Pemalang Indonesia through the School Literacy Movement program. The descriptive qualitative approach was used in this study. The study lasted from 18 October 2022 to 12 January 2023. Data was gathered through observation, interviews, and documentation. The data analysis technique includes three steps: data reduction, data display, and data verification. The findings revealed that several efforts were made in the classroom to improve students' reading literacy culture, including implementing a habituation program to read books before beginning learning, reading asma'ul husna, reading salawat, memorizing juz amma, providing reading corners, posterization, and procuring existing literacy trees. The literacy program was introduced in two stages. The first stage was carried out by reading asma'ul husna and salawat in the school yard, and the second stage was carried out by reading juz amma and developing reading habits before learning began. The impact of implementing the program is that students become accustomed to reading. The reading literacy program should be integrated into other school-based and community-based programs.